A Dinacharya Procedure as the Preventive Measure of Lifestyle Disorder in the Present Era: A Review Study - Bez, Jayashree (International Research Journal of Ayurveda & Yoga, 2022)
In the present era, man runs for the making money, to gain more profits and to avail all facilities in the pursuits of prosperity in order to lead a life of aristocracy. Keeping in view of these, man is adhered to heavy responsibilities, duties, physical and mental tensions and workloads. So, he suffers from many lifestyle disorders and mental illness. Ayurveda being a holistic health science emphasises on the importance of healthy & secured lifestyle by preventing lifestyle disorders. This present paper focuses on various aspects of Dinacharya described in Ayurveda and its applications in the present scenario for the maintenance of good health to prevent lifestyle disorder. It is a Review study based on certain narratives of dinacharya.